Continuing Education Center Administrators' Administrative Competence: Teachers' and Employee's Opinions - Balyer, Aydin; Ozcan, Kenan; Yildiz, Ali (ICLEL CONFERENCES, 2016)
Recent changes in university-industry relations have made continuing education centers become more important institutions. These centers provide many programs ranging from language courses to project management for both students, academics at university and people outside the campus. Therefore, the administration of these centers becomes more crucial. There is an administrative body, which manages all the programs as well as building relationships with the society at these centers. This study aims to determine the administrative competences of these administrators according to teachers' and employee's opinions. The research was conducted qualitatively and the participants of this study were 20 teachers and 20 employees chosen by maximum variation sampling method from different programs conducted at 5 Continuing/Lifelong Education Centers in Istanbul, (Istanbul University, Marmara University, Yildiz Technical University, Istanbul Technical University, and Bogazici University), Turkey, in the 2015/2016 academic year. Their views on their administrators' competencies decision making, managing programs, supporting staff professional development, developing relations with the society, evaluating and improving instruction and creating a positive learning environment and climate were researched. Results reveal that while administrators have competencies in all areas, they do not do much for staff professional development. It is recommended that administrators should support the staff development more.
Keywords: Continuing education; administrators; administrators' competencies; Education & Educational Research